Quorum sensing disruption regulates hydrolytic enzyme and biofilm production in estuarine bacteria. (16th October 2021) - Urvoy, Marion; Lami, Raphaël; Dreanno, Catherine; Daudé, David; Rodrigues, Alice M. S.; Gourmelon, Michèle; L'Helguen, Stéphane; Labry, Claire
Summary: Biofilms of heterotrophic bacteria cover organic matter aggregates and constitute hotspots of mineralization, primarily acting through extracellular hydrolytic enzyme production. Nevertheless, regulation of both biofilm and hydrolytic enzyme synthesis remains poorly investigated, especially in estuarine ecosystems. In this study, various bioassays, mass spectrometry and genomics approaches were combined to test the possible involvement of quorum sensing (QS) in these mechanisms. QS is a bacterial cell–cell communication system that relies notably on the emission of N ‐acylhomoserine lactones (AHLs). In our estuarine bacterial collection, we found that 28 strains (9%), mainly Vibrio, Pseudomonas and Acinetobacter isolates, produced at least 14 different types of AHLs encoded by various luxI genes. We then inhibited the AHL QS circuits of those 28 strains using a broad‐spectrum lactonase preparation and tested whether biofilm production as well as β‐glucosidase and leucine‐aminopeptidase activities were impacted. Interestingly, we recorded contrasted responses, as biofilm production, dissolved and cell‐bound β‐glucosidase and leucine‐aminopeptidase activities significantly increased in 4%–68% of strains but decreased in 0%–21% of strains. These findings highlight the key role of AHL‐based QS in estuarine bacterial physiology and ultimately on biogeochemical cycles. They also point out the complexity of QS regulations within natural microbial assemblages.